Young people, drugs and risk : an ethnography of drug use in a Dublin inner-city community - Mayock, Paula (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2004)
This ethnographic study of drug use is based in a socially disadvantaged Dublin locality with a lengthy history of concentrated drug problems. The study set out to investigate drug use and non-use among young people living in this 'high risk' social environment and to trace their drug 'journeys' as they move towards young adulthood. The study's longitudinal design incorporated two separate phases of fieldwork - the first conducted in 1998 and the second in 2001 - and involved active participation in the social milieu of young people, whether in youth clubs, on the street or, occasionally, in their own homes. At the core of the research was the question of how young people from one marginal 'zone' of Dublin's inner-city navigate the social landscapes available to them and form different kinds and levels of commitment to illicit drug consumption. In accordance with the study's aim of including a range of types and levels of drug involvement, three 'categories' of respondents - abstainers, drugtakers and problem drugtakers - were recruited and followed-up over the three-year study period. Individual in- depth interviews and focus group discussions were conducted, alongside regular contact with and participation within a range of neighbourhood settings.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin